Gender associated disparities in atrioventricular nodal reentrant tachycardia: A review article. (16th May 2021) - Etaee, Farshid; Elayi, Claude S.; Catanzarro, John; Delisle, Brian; Ogunbayo, Gbolahan; Di Biase, Luigi; Natale, Andrea; Darrat, Yousef
Abstract: Atrioventricular nodal reentrant tachycardia (AVNRT) is the most common sustained supraventricular arrhythmias. An understanding of gender‐related differences in AVNRT epidemiology, diagnosis, treatment, outcome, and complications can help guide a more effective diagnosis and treatment of the condition. The study aimed to perform a review of the available literature regarding all aspects of gender‐related differences of AVNRT. We focused on all aspects of gender‐related differences regarding AVNRT between men and women. A literature search was performed using Google Scholar, PubMed, Springer, Ovid, and Science Direct. Many investigations have demonstrated that the prevalence of AVNRT exhibited a twofold women‐to‐men predominance. The potential mechanism behind this difference due to sex hormones and autonomic tone. Despite being more common in women, there is a delay in offering and performing the first‐line therapy (catheter ablation) compared to men. There were no significant gender‐related discrepancies in patients who underwent ablation therapy for AVNRT, regarding the acute success rate of the procedure, long‐term success rate, and recurrence of AVNRT. AVNRT is more common in women due to physiological factors such as sex hormones and autonomic tone. Catheter ablation is equally safe and efficacious in men and women; however, the time between the onset of symptoms and ablation is significantly prolonged in women. It is important for the medical community to be aware of this discrepancy and to strive to eliminate such disparities that are not related to patients' choices.